2012
DOI: 10.5152/ttd.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Frequency in Patients Taking TNF-alpha Blokers

Abstract: Objective: To evaluate tuberculosis frequency in patients who take tumor necrosis factor alpha (TNF-a) inhibitors for Collagen Vascular Disease (CVD). Materials and Methods:Patients who actively use or were planned to use TNF-a inhibitors for CVD between June 2007-February 2010 were prospectively included in the study.All patients had a physical examination, chest x-ray and the Tuberculin Skin Test (TST). Sputum smear and culture for acid fast bacilli (AFB) was performed in patients with a suspicious lesion on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
8
0
3
Order By: Relevance
“…In another report from Japan, TB was found to develop in 13 out of 4,000 patients receiving these agents [30]. In contrast, there is a relative scarcity of data on the prevalence of TB in patients receiving aTNF-α-T in Turkey [5,19,20,21,22]. Hanta et al [20] reported 3 patients developing TB out of 192 who received aTNF-α-T. Elbek et al [5] concluded that aTNF-α-T is associated with a nearly 40-fold increased risk of TB after observing active TB in 2 of 240 subjects during the course of aTNF-α-T.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another report from Japan, TB was found to develop in 13 out of 4,000 patients receiving these agents [30]. In contrast, there is a relative scarcity of data on the prevalence of TB in patients receiving aTNF-α-T in Turkey [5,19,20,21,22]. Hanta et al [20] reported 3 patients developing TB out of 192 who received aTNF-α-T. Elbek et al [5] concluded that aTNF-α-T is associated with a nearly 40-fold increased risk of TB after observing active TB in 2 of 240 subjects during the course of aTNF-α-T.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, limited data from this country regarding the incidence of TB in patients undergoing aTNF-α-T suggests an 11-40 times higher risk of TB compared to the general population [5,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, with a background of serious TB epidemic experience during the first half of the 20th century, the country showed around 2‐fold diminishing TB incidence trend over last 25 years with a resultant incidence rate of 18/100 000 in an about 79 millions of population in 2016, but still considered among high‐priority countries by WHO . However, several studies reported substantial elevation of TB incidence associated with anti‐TNF‐α agents despite the presence of a risk management strategy . This requires evaluation of the TB risk at the national level that would not only reflect the relative risk (RR) but also help to address potential areas of development or contributions to existing risk management strategy.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…18,19 However, several studies reported substantial elevation of TB incidence associated with anti-TNF-α agents despite the presence of a risk management strategy. [20][21][22][23][24] This requires evaluation of the TB risk at the national level that would not only reflect the relative risk (RR) but also help to address potential areas of development or contributions to existing risk management strategy.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
See 1 more Smart Citation